1997
DOI: 10.1074/jbc.272.24.15562
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activation of Cholera Toxin and Escherichia coli Labile Toxin by Entry into Host Epithelial Cells

Abstract: Cholera and Escherichia coli heat-labile toxins (CT and LT) require proteolysis of a peptide loop connecting two major domains of their enzymatic A subunits for maximal activity (termed "nicking"). To test whether host intestinal epithelial cells may supply the necessary protease, recombinant rCT and rLT and a protease-resistant mutant CTR192H were prepared. Toxin action was assessed as a Cl ؊ secretory response (Isc) elicited from monolayers of polarized human epithelial T84 cells. When applied to apical cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 32 publications
3
52
0
Order By: Relevance
“…Moreover studies with human intestinal T84 cell lines have demonstrated that the presence of an unidentified host epithelial serine protease(s) is sufficient to process CT A (85). In light of these findings, it is very likely that host proteases are responsible for CT A activation during intestinal colonization of V. cholerae; however, there may be conditions, yet to be determined, during which Vibrio proteases such as VesA and HapA play significant roles in the processing and activation of CT A.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover studies with human intestinal T84 cell lines have demonstrated that the presence of an unidentified host epithelial serine protease(s) is sufficient to process CT A (85). In light of these findings, it is very likely that host proteases are responsible for CT A activation during intestinal colonization of V. cholerae; however, there may be conditions, yet to be determined, during which Vibrio proteases such as VesA and HapA play significant roles in the processing and activation of CT A.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Etx from enterotoxinogenic E. coli, as well as recombinant Ctx produced in E. coli, are normally isolated with their A-subunits intact; trypsin or other gut-associated proteases have been postulated to accomplish toxin activation in such cases (33). Recent studies on T84 cells have shown that a serine protease, which efficiently nicks and activates both CtxA and EtxA, is present on either the apical surface or in apicallyderived transport vesicles (31). In this respect, no difference was found in toxicity of commercial (nicked) preparations of Ctx and recombinant Ctx that was either unnicked or nicked with trypsin.…”
mentioning
confidence: 80%
“…For Ctx and Etx to exhibit full toxicity, the A-subunits must undergo proteolytic cleavage or "nicking" at Arg-192 to give separate A1-and A2-fragments (31). In the case of cholera toxin, extracellular proteases, such as HA protease produced by V. cholerae, can efficiently nick and activate the A-subunit (32).…”
mentioning
confidence: 99%
“…Receptor binding is followed by internalization of LT into vesicles which are retrograde transported to the Golgi apparatus and endoplasmic reticulum (Rappuoli et al, 1999). Proteolytic cleavage of the A subunit into A 1 and A 2 domains (Lencer et al, 1997) occurs and is followed by the translocation of the A 1 domain into the cytosol. The A 1 domain ADPribosylates the -unit of the G s protein, the G protein regulating the activity of adenylate cyclase, resulting in the permanent activation of adenylate cyclase (Rappuoli et al, 1999) which in turn causes abnormal increases in cyclic AMP (cAMP) levels (Nataro et al, 1998).…”
Section: Lt Toxinmentioning
confidence: 99%